Implementasi Aplikasi Jakarta Kini Dalam Meningkatkan Pelayanan Masyarakat Di Kelurahan Kampung Bali Kecamatan Tanah Abang Kota Administrasi Jakarta Pusat - Sukma Perdana, Redy Firmansyah (Jurnal Syntax Fusion, 2023)
The Jakarta Kini (JAKI) application is a digital information technology for governance and community service improvement. It provides a survey mechanism for assessing the performance of the Mayor/Head of District, Head of Sub District, and Head of Urban Village in the DKI Jakarta Provincial Government. Through this application, feedback can be provided to improve governance and public services. The purpose of this research is 1). To analyze and evaluate the implementation of the Jakarta Kini (JAKI) application to improve community service in Kampung Bali Urban Village, Tanah Abang Sub District, Central Jakarta Administrative City, 2). To analyze and evaluate the obstacles in implementing the Jakarta Kini (JAKI) application to improve community service in Kampung Bali Urban Village, Tanah Abang Sub District, Central Jakarta Administrative City. 3). To analyze and evaluate the efforts in implementing Jakarta Kini (JAKI) implementation to improve community service in Kampung Bali Urban Village, Tanah Abang Sub District, Central Jakarta Administrative City. The research used qualitative methods to reveal in-depth qualitative data through interviews, observation, and desk study. The result of the study showed that implementation of Jakarta Kini (JAKI) application in Kampung Bali Urban Village, Tanah Abang Sub District, Central Jakarta Administrative City, to improve community service has been successfully implemented.